The Effect of Different Orthodontic Force on MMP 9 Expression in a Rat Diabetic Model - Hafiedz Maulana; Nuzulul Hikmah; Amandia Dewi permana Shita; Nur Permatasari; Sri Widyarti (Journal of Tropical Life Science, 2014)
Orthodontic forces produce alveolar bone and periodontal ligament remodeling that cause tooth movement. Diabetes can increase tissue damage and, therefore, contributes to the process of orthodontic tooth movement. The aim of this study was to determine the effect of differently orthodontic forces on the expression of MMP nine in rat diabetic model. Twenty four male Wistar rats were divided into three groups of control and three groups of treatment streptozotocin-induced diabetes with stratified doses. Application of orthodontic appliance was performed with different forces (10, 20 and 30 grF). Orthodontic appliance was performed on both upper incisors. Immunohistochemical (IHC) analysis was used to observe the expression of MMP 9 and HE (Hematoxylen Eosin) staining to observe the number of fibroblasts. Statistical analysis was carried out using t-test and Spearman correlation analysis to determine the difference of MMP nine expression and number of fibroblasts between groups, and determine the correlation of both. The results showed an increased expression of MMP 9 and decreased of fibroblasts number in diabetic rats, along with increasing magnitude of orthodontic forces. The different orthodontic forces given to diabetic rats affect the expression of MMP 9 and the number of fibroblasts, in which the expression of MMP 9 increased along with the increase of orthodontic forces, both at pressure and tension sides.